Dynamic tracking of human umbilical cord mesenchymal stem cells (huc-mscs) following intravenous administration in mice model - Chin, Sze-Piaw; Marzuki, Marini; Tai, Lihui; Mohamed Shahrehan, Nurul Ashikin; Ricky, Christine; Fanty, Audrey; Salleh, Annas; Low, Chui Thean; Then, Kong-Yong; Hoe, Susan Ling Ling; Cheong, Soon Keng (Elsevier BV, 2024)
Abstract not available.